2005
DOI: 10.1159/000089053
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nitric Oxide in Amniotic Fluid of Patients with Chorioamnionitis

Abstract: Objective: Levels of nitric oxide (NO) and cytokines were assessed in amniotic fluid obtained from patients with severe chorioamnionitis (CAM) and appropriate controls. Methods: Amniotic fluid was obtained from 12 patients with CAM (17–24 weeks of gestation) and 89 patients undergoing diagnostic amniocentesis (16–18 weeks of gestation). The concentrations of NO, interleukin-6 (IL-6), and leukocyte elastase (LE) in amniotic fluid were then measured and compared. Results: The concentrations of NO, IL-6, and LE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Chorioamnionitis causes a strong proinflammatory response, and fetal exposure to these cytokines presented in amniotic fluid has been associated with an increased risk of chronic lung disease. 22,23 On the basis of these studies, it seems likely that at least in some patients, the development of asthma could be a result of early subclinical or clinical chorioamnionitis at the time of birth through inflammatory mechanisms. It is also possible that early neonatal infection caused by bacterial colonization during delivery could be more probable in those children who are genetically more prone to allergy and asthma with a defective innate immune response in the early phase of life.…”
Section: Discussionmentioning
confidence: 99%
“…Chorioamnionitis causes a strong proinflammatory response, and fetal exposure to these cytokines presented in amniotic fluid has been associated with an increased risk of chronic lung disease. 22,23 On the basis of these studies, it seems likely that at least in some patients, the development of asthma could be a result of early subclinical or clinical chorioamnionitis at the time of birth through inflammatory mechanisms. It is also possible that early neonatal infection caused by bacterial colonization during delivery could be more probable in those children who are genetically more prone to allergy and asthma with a defective innate immune response in the early phase of life.…”
Section: Discussionmentioning
confidence: 99%
“…According to Daoud et al . patients with chorioamnionitis had increased NO metabolites in amniotic fluid compared to patients without chorioamnionitis 33 . But according to Chwalisz and Garfield a decrease in NO production in the uterus contributes to the initiation of labor, whereas in the cervix NO acts as a final metabolic mediator of cervical ripening 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This study is in agreement with Ananias and Yano (23) who found that nearly 5% of strains were positive for papC and other were negative, suggesting that other adhesive gene was present or papC may be deleted. Also, Daoud et al, (24), have isolated twenty isolates from various clinical material (urine, vagina, and rectal swab), and it has been found that three isolates gave papC and the others did not produce it. sfa located within PAIs was observed in only three isolates The distribution of the sfa found among the isolates studied was higher than previous studied by Santo et al, (25) who reported that only one isolate of E. coli bear this gene.…”
Section: Junmentioning
confidence: 99%